ECOLOGICAL TESTING OF GRAIN SORGHUM VARIETIES AND HYBRIDS - N. A. Kovtunova; V. V. Kovtunov; A. V. Baranovsky; A. E. Romanyukin; E. A. Shishova (Зерновое хозяйство России, 2018)
The Lugansk region is situated in the arid steppe part, where the main grain crops are not able to realize productive potential to their full extent. The purpose of the work is to identify the features of grain sorghum varieties developed by the FSBSI ARC “Donskoy” in the conditions of the Lugansk region. The objects of the study were the sorghum varieties ‘Orlovskoe’, ‘Zernogradskoe 88’, ‘Luchistoe’, ‘Velikan’, ‘Khazine 28’ developed by the FSBSI ARC “Donskoy” in comparison with the varieties and hybrids of exotic breeding. The ecological study was conducted in the experimental plot of the Lugansky National Agricultural University in 2016–2017. The varieties selected by the ARC “Donskoy” belong to the groups of ultra-early season and early season varieties and become completely mature for 83–96 days. The productivity of the varieties ‘Orlovskoe’, ‘Luchistoe’, ‘Velikan’ is similar to the productivity of varieties and hybrids which mature on 20–25 days later. The varieties manage to form high-grade grain to mid-September and do not need any costs on desiccation of sowings and drying of grain after harvesting to conventional humidity that testifies high economic efficiency of the ARC “Donskoy” varieties. Grain productivity is a complex trait, which consists of various quantitative elements. The conducted structural analysis showed that plant height, 1000-kernel weight, grain nature of the most varieties and hybrids had week correlation with external conditions. According to the correlation-regression analysis grain nature in the Lugansk region is directly connected with sorghum productivity. The increase of grain nature on one unit results in grain productivity increase on 0.0091 t/ha.